Sedentary lifestyle as a risk factor for cardiovascular diseases in young people: awareness, self-assessment and stress test results - E. I. Zimakova; A. G. Plisyuk; Yu. L. Begrambekova; D. A. Rybakov; I. Sh. Daudov; Y. A. Orlova (Кардиоваскулярная терапия и профилактика)
Aim. A comprehensive study of sedentary lifestyle in young people at different levels: awareness of the connection between physical activity and the risk of cardiovascular diseases, self-assessment of physical activity and impartial evaluation of cardiorespiratory endurance.Material and methods. The study included 112 students aged 18 to 24 years without verified noncommunicable diseases, who filled out the "Questionnaire for individuals aged <65 years to identify noncommunicable diseases, risk factors for their development, consumption of narcotic drugs and psychotropic substances without prescription" and an additional questionnaire with open questions about cardiovascular risk factors. In addition, participants underwent the Harvard step test.Results. The level of cardiorespiratory endurance was not associated with sex and age in our sample. There was also no significant association between a high Harvard step test score and a positive response to the question about moderate or brisk walking >30 min/day. A positive response about training (3 times/week) in 3/4 of cases identified young people with average and high cardiorespiratory endurance.Conclusion. The study results indicate a fairly high awareness of students about the dangers of physical inactivity. The data obtained can form the basis for research to optimize methods for assessing the physical activity of young people, used as part of the first stage of medical examination.